2021
DOI: 10.11106/ijt.2021.14.1.42
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hyperparathyroidism Caused by Intrathyroidal Parathyroid Adenoma

Abstract: Hyperparathyroidism is a common endocrine disorder, but intrathyroidal parathyroid adenoma is extremely rare. We report a on a case of hyperparathyroidism caused by intrathyroidal parathyroid adenoma. This case is important in that it affects an effective test for the diagnosis of intrathyroidal parathyroid adenoma, and shows the decision of the treatment process and the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Patients with intrathyroidal parathyroid adenomas can present with overt symptoms of primary hyperparathyroidism, or can be asymptomatic 9,24,25 . Symptoms of hypercalcemia are wide‐ranging and can include bone pain, polyuria, renal colic, constipation, and depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with intrathyroidal parathyroid adenomas can present with overt symptoms of primary hyperparathyroidism, or can be asymptomatic 9,24,25 . Symptoms of hypercalcemia are wide‐ranging and can include bone pain, polyuria, renal colic, constipation, and depression.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with intrathyroidal parathyroid adenomas can present with overt symptoms of primary hyperparathyroidism, or can be asymptomatic. 9 , 24 , 25 Symptoms of hypercalcemia are wide‐ranging and can include bone pain, polyuria, renal colic, constipation, and depression. In a cohort of 53 IPAs, Mazeh et al found no difference in the type of clinical symptoms, demographics, and blood results relative to a control group of normal parathyroid adenomas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is usually diagnosed preoperatively by biochemical changes, ultrasound and nuclear imaging as well as per operatively by frozen section examination and parathyroid hormone levels after excision. 4 But sometimes parathyroid glands are difficult to recognize macroscopically during operation and turn to be thyroid tissue by frozen section examination. Again, in case of ectopic location, parathyroid gland may not be found even after meticulous search.…”
Section: Introductionmentioning
confidence: 99%